2020
DOI: 10.1097/md.0000000000020976
|View full text |Cite
|
Sign up to set email alerts
|

Ward nurses-focused educational intervention improves the quality of bowel preparation in inpatients undergoing colonoscopy

Abstract: Background: Adequate bowel preparation is essential for the detection of pathological lesions during colonoscopy. However, it has been found to be inadequate in approximately 20% to 30% of colonoscopy examinations. Educational interventions focused on health staff, such as physicians and nurses, may improve the patients’ understanding of the bowel preparation instructions, and consequently, increase the quality of bowel preparation. Objectives: To investigate whether en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Previous studies had explored the impact of education on the quality of bowel cleansing (20)(21)(22), which confirmed the effectiveness of patient education programs. Liu's study (23) also revealed that inpatients under the care of nurses who underwent enhanced education on bowel preparation had a significantly better bowel preparation quality, and ward nurses' education was the only independent risk factor, considering that the bowel preparation of inpatients was often guided by the nurses whereas that of outpatients was always guided by the referring physicians. We believed that verbal instructions accompanying written ones for outpatients seem to ameliorate the results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had explored the impact of education on the quality of bowel cleansing (20)(21)(22), which confirmed the effectiveness of patient education programs. Liu's study (23) also revealed that inpatients under the care of nurses who underwent enhanced education on bowel preparation had a significantly better bowel preparation quality, and ward nurses' education was the only independent risk factor, considering that the bowel preparation of inpatients was often guided by the nurses whereas that of outpatients was always guided by the referring physicians. We believed that verbal instructions accompanying written ones for outpatients seem to ameliorate the results.…”
Section: Discussionmentioning
confidence: 99%
“…One potential solution to improve ABP in the hospital setting is to prioritize preprocedural clinician meetings [12]. Ongoing clinical education is also recommended and can include hospital lectures and initiatives on prompt symptom identification, appropriate referrals, standardized order sets, and improved preprocedural readiness assessments [19][20][21]. Further research in this topic is warranted and these results suggest interventions may be increasingly effective when identifying hospitalized patients with a history of opioid use, laxative use, or constipation.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have this for our study; however, we believe this would be helpful for other institutions when implementing research or evidence-based practice projects related to inpatient colonoscopies. Another study also looked at an educational intervention focused on ward nurses (Liu et al, 2020). Their education was similar to ours although they had a physician teach inpatient nurses.…”
Section: Discussionmentioning
confidence: 99%